Maruja Mallo: Artist, Chronicler, Surrealist? - Fernández Luccioni, Manuel (Madrygal. Revista de Estudios Gallegos, 2012)
This article comes to wonder whether from Artistic History should be considered Maruja Mallo as a Surrealist painter, and if so would cover all or part of her work making overview of her career until her early works in Latin America.